2021
DOI: 10.3390/ani11123387
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection and Genotyping of Enterocytozoon bieneusi in Black Goats (Capra hircus) in Yunnan Province, Southwestern China

Abstract: Enterocytozoon bieneusi is a fungus-like protist that can parasitize in the intestines of humans and various animals causing a threat to public health. However, there has been no data for E. bieneusi prevalence and genotypes in black goats in Yunnan Province, Southwestern China. In this study, 907 fecal samples were collected from black goats in 5 counties from Yunnan Province. The prevalence and genotypes of E. bieneusi were examined by nested PCR amplification targeting the nuclear internal transcribed space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(66 reference statements)
1
2
0
Order By: Relevance
“…A sequence analysis based on the ITS gene locus of 112 E. bieneusi isolates revealed nine known genotypes (CHG3, CHG1, BEB6, CHG5, CHG2, SX1, CHG28, COS-II and CD6) in goat kids in the present study, and these genotypes have been previously reported in sheep and goats [32,[70][71][72]. Among the identified genotypes in this study, CHG3 was the most common genotype, which was also found in goats from Henan, Yunnan, Anhui, Chongqing and Shaanxi, as well as in sheep in Henan [71].…”
Section: Discussionsupporting
confidence: 81%
“…A sequence analysis based on the ITS gene locus of 112 E. bieneusi isolates revealed nine known genotypes (CHG3, CHG1, BEB6, CHG5, CHG2, SX1, CHG28, COS-II and CD6) in goat kids in the present study, and these genotypes have been previously reported in sheep and goats [32,[70][71][72]. Among the identified genotypes in this study, CHG3 was the most common genotype, which was also found in goats from Henan, Yunnan, Anhui, Chongqing and Shaanxi, as well as in sheep in Henan [71].…”
Section: Discussionsupporting
confidence: 81%
“…However, genotypes and prevalence rates probably also differ by region. This is the first report of E. bieneusi in black goats in Guangdong Province, with a prevalence of 17.7% (40/226), which is lower than in Egypt (100%, 11/11) [37], Thailand (19.2%, 14/73) [38], Henan (66.7%, 104/156; 50.7%, 73/144; 32.9%, 113/343) [15,39,40], Chongqing (62.5%, 5/8) [40], Shaanxi (47.8%, 22/46; 21.9%, 106/485) [15,40], the Ningxia Autonomous Region (29.7%, 89/300) [41], Yunnan (22.4%, 30/134) [40], Heilongjiang (21.8%, 12/55) [42], and Qinghai (18.6%, 11/59) [43], but higher than in Slovakia (0%, 0/20) [44], Shandong (0%, 0/24) [45], Jiangsu (2.7%, 2/74) [45], Anhui (5.2%, 30/574; 7.5%, 6/80) [40,45], Yunnan (8.93%, 30/336; 10.3%, 93/907) [34,36], and the Tibet Autonomous Region (9.6%, 25/260) [46]. These results indicate the importance of goats as hosts for E. bieneusi and their potential role in transmitting microsporidiosis caused by this parasite.…”
Section: Discussionmentioning
confidence: 90%
“…Enterocytozoon bieneusi is an emerging zoonotic intestinal pathogen that infects humans and many animal species. Many studies have identified and genotyped E. bieneusi in black goats throughout the world [34][35][36][37]. The infection rate of E. bieneusi in goats ranges from 0 to 100% worldwide, and the overall prevalence in goats is estimated to be 16.3% [14].…”
Section: Discussionmentioning
confidence: 99%